Acute peripheral tissue effects of ghrelin on interstitial levels of glucose, glycerol, and lactate: a microdialysis study in healthy human subjects - Vestergaard, Esben Thyssen; Møller, Niels; Jørgensen, Jens Otto Lunde (American journal of physiology: endocrinology and metabolism, 2013)
Ghrelin is a gut-derived peptide and an endogenous ligand for the ghrelin receptor. Intravenous infusion of ghrelin induces insulin resistance and hyperglycemia and increases circulating levels of nonesterified free fatty acids. Our objective was to investigate whether the metabolic effects are mediated directly by ghrelin in skeletal muscle and adipose (peripheral and central) tissues. Ten healthy men (24.9 ± 1.3 yr) received 300 min of supraphysiological ghrelin administration by microdialysis catheters in skeletal muscle and adipose tissues in a randomized, single-blind, and placebo-controlled study. Microdialysis perfusates were analyzed every 30 min for glucose, glycerol, and lactate during both a basal period and a hyperinsulinemic euglycemic clamp. The primary outcome measures were interstitial concentrations of glucose, glycerol, and lactate in skeletal muscle and adipose tissues. Interstitial concentrations of glucose were similar in skeletal muscle, peripheral, and central adipose tissue in the basal period. During hyperinsulinemia, interstitial concentrations of glucose in skeletal muscle decreased in response to ghrelin exposure [2.84 ± 0.25 (ghrelin) vs. 3.06 ± 0.26 mmol/l (placebo), P = 0.04]. Ghrelin exposure did not impact on interstitial concentrations of glycerol and lactate. We conclude that ghrelin administration into skeletal muscle decreases interstitial concentrations of glucose during euglycemic hyperinsulinemia, which is indicative of increased insulin sensitivity without any effects on interstitial glycerol levels in either muscle or adipose tissue. These data contrast with the metabolic effects of ghrelin observed after systemic exposure and suggest the existence of a second messenger that remains to be identified.